ميزة التقنين والإجراءات المتبعة في التقاضي في شريعة حمورابي - العدواني, ليلى (جامعة الوادي - University of Eloued, 2019)
The law of Hammurabi is one of the oldest laws known to humanity, although not the oldest ones, preceded by other laws such as the law of Ishtar and Ashnuna, etc. It is the most famous and thanks to it Hammurabi became the most famous of the Mesopotamian kings. Historians relied on it for social, In this civilization, and it has been the focus of many studies, but this study is different in that it tries to shed light on the law itself to know the characteristics that characterized the formulation of the texts and procedures of litigation, especially as it is the result of the collection of laws that preceded it with some amendments and additions that Which is appropriate to the needs of Hammurabi's rule, although he claimed the divinity of its source to give sanctity to it. The importance of knowing the advantage of codification and litigation in the law of Hammurabi is that it will give us an idea of the progress made by the human mind at that time in the development of legal texts, And the organization of this civilization and its rich heritage and human thought, and what may have affected it in the subsequent legislation, even in modern laws, this study is considered to be an indication of the accumulation of human experience that led to the development of the law and the procedures of litigation with the succession of civilizations.
مقال